Activization of schoolchildren’s cognitive activity during labor training classes: experiment results (Pedagogy of Higher and Secondary Education, 2014)
Sushentsev O. Ye. Activization of schoolchildren’s cognitive activity during labor training classes: experiment results.The author reveals the course of test work on checking theoretically defined pedagogical conditions of promoting cognitive activity of schoolchildren during labor training classes
Keywords: activization of cognitive activity; cognitive activity; cognitive independence; labor training